Peran Lembaga Zakat dalam Pendampingan Bisnis Mustahik Sebagai Upaya Peningkatan Kesejahteraan Penerima Zakat: Studi Kasus LAZISMU Malaysia - Sutrisno, Sutrisno (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research was to determine how to optimize the role of LAZISMU Malaysia in supporting the businesses of zakat recipients, as a means to improve the welfare of the mustahik (zakat beneficiaries). This research was a descriptive qualitative study, with data collected through observation, interviews, and documentation review. The research findings concluded that LAZISMU Malaysia has played an active coaching role for small business activities run by zakat recipients. This role is carried out through a mentoring program for mustahik facing difficulties managing their business and capital to increase business income. The steps taken to assist zakat recipients include guidance on managing finances simply by applying an income and expenditure accounting model. Further assistance provided by LAZISMU Malaysia to boost mustahik income involved marketing training in collaboration with Muhammadiyah universities community services in Malaysia. Additionally, LAZISMU Malaysia provides support through the smart display program (arranging business premises) using a modern market approach prioritizing cleanliness, comfort, convenience, and friendliness for all customers. By assisting the businesses of zakat recipients, the mustahik can increase the income generated from the enterprises they run. Keywords: Role of Zakat Institutions, Business Assistance, Improving Welfare.